Play-hysteresis in supply as part of a market model - Göcke, Matthias; Justus Liebig University Giessen (My University, 2012)
Consequences of path-dependent supply side on the market equilibrium are illustrated. Supply is only a subsystem of the entire market with its forcing variable (price) being endogenous from the perspective of the entire market. This results in feedbacks on the equilibrium of price and quantity if transient exogenous disturbances occur. Aggregate hysteresis is modelled by continuous dynamics showing similarities to 'mechanical play'. This contrast the standard firm level modelling of hysteresis resulting from discontinuous (activity/inactivity) switches. Play dynamics are captured in a simple linearized way, just by adding two parameters to a supply equation.
Keywords: path-dependence; play-hysteresis; modelling techniques; ddc:650